(untitled) (Research, Society and Development, 2019)
This study aims to identify in the available literature whether the care provided to patients in the emergency and emergency is humanized. The integrative literature review was used as a methodology, based on the findings of the articles published in the temporal cut from 2007 to 2017. Finally, the analysis of 07 scientific articles was analyzed and categorized and discussed, according to the Bardin Content Analysis. In the results, it was verified that the humanized care is of extreme importance, to pass security, to give a smile, to look into the eyes, to know the history of the patient, are simple attitudes, but that make the difference in the care provided to the patient. However, it has been identified that such actions do not always occur, due to lack of employees, demands, lack of resources and even physical and psychological wear and tear. Therefore, it is concluded that in the search for excellence in nursing care, it is necessary for the professional to possess the technical and scientific knowledge, without forgetting the feelings and needs of the patients.